Epigenetic Regulation of Angiogenesis by JARID1B-Induced Repression of HOXA5. Issue 7 (July 2015) - Fork, Christian; Gu, Lunda; Hitzel, Juliane; Josipovic, Ivana; Hu, Jiong; SzeKa Wong, Michael; Ponomareva, Yuliya; Albert, Mareike; Schmitz, Sandra U.; Uchida, Shizuka; Fleming, Ingrid; Helin, Kristian; et al.
Abstract : Objective—: Altering endothelial biology through epigenetic modifiers is an attractive novel concept, which is, however, just in its beginnings. We therefore set out to identify chromatin modifiers important for endothelial gene expression and contributing to angiogenesis. Approach and Results—: To identify chromatin modifying enzymes in endothelial cells, histone demethylases were screened by microarray and polymerase chain reaction. The histone 3 lysine 4 demethylase JARID1B was identified as a highly expressed enzyme at the mRNA and protein levels. Knockdown of JARID1B by shRNA in human umbilical vein endothelial cells attenuated cell migration, angiogenic sprouting, and tube formation. Similarly, pharmacological inhibition and overexpression of a catalytic inactive JARID1B mutant reduced the angiogenic capacity of human umbilical vein endothelial cells. To identify the in vivo relevance of JARID1B in the vascular system, Jarid1b knockout mice were studied. As global knockout results in increased mortality and developmental defects, tamoxifen-inducible and endothelial-specific knockout mice were generated. Acute knockout of Jarid1b attenuated retinal angiogenesis and endothelial sprout outgrowth from aortic segments. To identify the underlying mechanism, a microarray experiment was performed, which led to the identification of the antiangiogenic transcription factor HOXA5 to be suppressed by JARID1B. Importantly, downregulation or inhibition of JARID1B, but not of JARID1A and JARID1C, induced HOXA5 expression in human umbilical vein endothelial cells. Consistently, chromatin immunoprecipitation revealed that JARID1B occupies and reduces the histone 3 lysine 4 methylation levels at the HOXA5 promoter, demonstrating a direct function of JARID1B in endothelial HOXA5 gene regulation. Conclusions—: JARID1B, by suppressing HOXA5, maintains the endothelial angiogenic capacity in a demethylase-dependent manner. Abstract : Supplemental Digital Content is available in the text.